(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
With the urbanization process, anthropic procedures occur so that it can carry out construction of roads and buildings, in which they can use inappropriate areas for this occupation. The present investigation aimed to identify and understand the behavior of the geological risk areas of Filadélfia neighborhood, in the well-known expansion Alegria De Teófilo Otoni-Minas Gerais, which has land with irregular topography and slopes even greater than 100%. In view of this situation, the brief literature review was carried out seeking theoretical and technical basis to carry out the survey of 3 specific points in the place, carrying out an on-site visit and classifying as to the existing risks. The situation in the 3 points in common with risk R3 (High Risk) was notorious, having fissures, cracks and even ravines in specific points of the slopes analyzed, which can cause landslides in the event of rainy periods.